Transfer of 'Engineer's Mind': Kim Choong-Ki and the Semiconductor Industry in South Korea. Issue 2 (4th May 2019) - Kim, Dong-Won
ABSTRACT: By the mid-2000s, South Korea had become a dominant power in semiconductors, and by the mid-2010s, its worldwide market share of memory had climbed to over 60%. Many scholars have endeavored to discover the secret of the South Korean success but have usually emphasized the roles and contributions of the South Korean government and individual companies in the development of semiconductors, almost totally neglecting those of the South Korean academy. This article analyzes how the South Korean academy contributed to the development and success of the semiconductor industry by examining the life and work of Kim Choong-Ki of Korea Advanced Institute of Science and Technology (KAIST). Beginning in 1975, Kim trained the first two generations of semiconductor engineers at KAIST, most of whom became the field's leading figures in academia, at research institutes, and especially in industry. This study is not a biography of Kim but a critical analysis of how a university professor, not an entrepreneur, became the 'godfather' of the semiconductor industry in South Korea. I argue that this was only possible within South Korea's unique triangular relationship among government, industry, and academia during the last quarter of the twentieth century.